Optimization of digital marketing strategy through e-commerce is increasing SME sales Batik Cikadu, Tanjung Lesung, Pandeglang - Prasetya, Prita; Widyanti, Winda; Rosdiana, Riska; Mahliza, Febrina; Oktasari, Dian Primanita (Priviet Social Sciences Journal, 2022)
Digital marketing is one strategy that business actors can do to promote their business. This community service activity is in the form of training on optimizing digital marketing strategies through E-commerce to increase sales of SME Batik Cikadu, Tanjung Lesung, Pandeglang. Batik Cikadu is one of the creative industries that has experienced a decline in sales due to the pandemic. This training was held face-to-face in the Tanjung Lesung Special Economic Zone (SEZ), Pandeglang Regency, Banten. The training method is in the form of material presentation, followed by discussion and question and answer. The results of this training show the participants' enthusiasm by providing understanding and practical examples in making marketing strategies through social media. With this activity, each group member gains knowledge and experience in digital marketing through e-commerce to make it easier for SMEs to increase brand knowledge to consumers and sales.